EDWARD JONES'S 'ENGLISH SYSTEM OF BOOKKEEPING' - Yamey, Basil S. (The Accounting Review, 1944)
Abstract In 1796, writer Edward Jones's "The English System of Book-keeping" was published in Bristol. The first edition contains a list of over 4,000 subscribers resident in all parts of Great Britain. The Bank of England and the Honourable East India Company each subscribed for five copies. The author is said to have profited to the extent of 25,000 pounds from his invention. His system is stated to have been widely used in both Great Britain and the U.S. It gained an international reputation in a short while, and is probably the only English work on accounting. The publication of the book was preceded in 1795 by "An Address to Bankers, Merchants, Tradesmen and others, intended as an introduction to a New System of Book-keeping." This address contents reproduced as an Introductory Address in the main work, sets out in the author's compelling style faults, demerits and positive dangers of the existing bookkeeping methods, both by single and double entry, without so much as giving a foretaste of the magnificent new system about to be made known to the long suffering commercial world.